HEARING AID EFFECTIVENESS ON PATIENTS WITH CHRONIC TINNITUS AND ASSOCIATED HEARING LOSS : SYSTEMATICS REVIEW - Triyanti, Yuli (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Tinnitus, the perception of sound in the absence of an obvious external source, is even more frequent, affecting around ten percent of adults in the United States. Tinnitus is defined as the sense of sound in the absence of an obvious external source. Tinnitus is typically accompanied by hearing loss, but this is not always the case. It is conceivable for it to occur either by itself or in conjunction with a loss of hearing of any type. Tinnitus and hearing loss are both caused by a wide variety of conditions, the most frequent of which is age-related hearing loss. Other, less common causes include malignancies of the brain and skull base. Hearing loss can be broken down into three basic categories: sensorineural, conductive, or mixed (where both conductive and sensorineural components are present). The perception of sound in the absence of external acoustic stimulation for an extended length of time (more than three months) is the hallmark of chronic tinnitus. Tinnitus is quite common, with an estimated incidence of 10–15% in the adult population; however, prevalence estimates can vary widely from study to study. Tinnitus is characterized by a buzzing or ringing sound in the ear. A minority of people may experience severe psychological distress as a direct result of the situation, despite the fact that the majority of people are able to adapt to the perception and report very mild emotional distress as a result of it. Tinnitus Questionnaire (abbreviated as TQ), Tinnitus Handicap Inventory (abbreviated as THI), and Tinnitus Functional Index (abbreviated as TFI) are the three self-report questionnaires that are used the most frequently for quantifying tinnitus-related suffering. The total scores of these measures properly capture both the suffering associated with tinnitus and the change that is attributable to treatments. In patients who have tinnitus and chronic hearing loss, the use of hearing aids is successful in suppressing the symptoms; however, the usage of the device must be carried out for at least six months in order for the treatment to take effect.